Implementation of the Social Security Administration (BPJS) Health Program in Healthcare Services at UPTD Public Health Center III, North Denpasar Sub-District Health Office - Putu Suartama; I Kadek Dede Junaedy; I Wayan Astawa (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
BPJS Kesehatan is a legal entity responsible for administering social security programs in accordance with Law Number 40 of 2004 on the National Social Security System. Community health centers (Puskesmas) play a strategic role in providing primary healthcare services, including in Denpasar, Bali, where numerous Puskesmas serve as primary healthcare facilities. However, the implementation of BPJS Kesehatan programs in Puskesmas faces several challenges, such as limited healthcare personnel, inadequate infrastructure, and an underdeveloped management system. Additionally, there is still a public perception that BPJS services can only be utilized when one is ill. This study employs a qualitative descriptive approach to analyze the implementation of healthcare services at UPTD Puskesmas III in North Denpasar District. The findings indicate that implementation is not yet fully optimal based on indicators of communication, resources, disposition, and bureaucratic structure. Key obstacles include insufficient BPJS outreach to the public, lack of significant improvements in service quality, as well as infrastructure limitations such as parking space, waiting areas, and noise disturbances due to the Puskesmas’ location in a densely populated area.